IMPLEMENTATION OF WORK DISCIPLINE IN IMPROVING PERFORMANCE OF KARAWANG STATE COURT EMPLOYEES CLASS 1 B - Hana Febrianti; Nandang; Zenita Apriani (Enrichment : Journal of Management, 2022)
The Karawang District Court is a general judicial environment under the Supreme Court of the Republic of Indonesia as the executor of independent judicial powers to administer justice in upholding Law and Justice, the Karawang District Court as the "front guard" (Voorj post) of the Supreme Court, has the duty and authorityreceive, examine, decide and settle cases that are entered at the first level. This study aims to find out and analyze how the work discipline of Karawang District Court employees, find out and analyze how the performance of Karawang District Court employees, and to find out how the implementation of work discipline to improve employee performance in the Karawang District Court Office Class 1 B. The type of research used by the author namely descriptive qualitative research. This study uses 2 kinds of data sources, namely primary data sources and secondary data sources. Data collection techniques used in the form of observation or direct observation, documentation, and interviews and the data analysis technique is using triangulation of data sources. The data is processed properly so that it becomes a tool of information that can be concluded. The results of the research and discussion show that the implementation of employee work discipline is good in terms of employee work targets and employee performance appraisals achieved, although it is inseparable from several shortcomings. In the future, it is hoped that the application of work discipline to Karawang District Court employees will be further improved in order to maximize employee performance so that organizational or agency goals can be achieved.